Effect of Kirganelia reticulata extract on Human Embryonic Kidney cells with evidence on morphological changes - Madhurima Ghosh, Jhinuk Chatterjee, V. Krishnamurthy (Journal of Applied Pharmaceutical Science, 2018)
Kirganelia reticulata has been proven to have cytotoxic activities. The aim of this study is to demonstrate the anti-proliferative activity of the methanolic extract of K. reticulata on Human Embryonic Kidney cells (HEK-293). Changes in cellular morphology of HEK-293 cells were evident at higher concentration and with an increase in time, which was supported by our experimental data. Our preliminary data suggest that K. reticulata methanolic extract has anti-proliferative activity.
Keywords: Phytochemicals, Kirganelia, HEK-293, Cell morphology, Anti-Proliferative.